STUbLs in chromatin and genome stability1. Issue 2 (22nd November 2012) - Garza, Renee; Pillus, Lorraine; Trievel, Ray
Abstract Chromatin structure and function is based on the dynamic interactions between nucleosomes and chromatin‐associated proteins. In addition to the other post‐translational modifications considered in this review issue of Biopolymers, ubiquitin and SUMO proteins also have prominent roles in chromatin function. A specialized form of modification that involves both, referred to as SUMO‐targeted ubiquitin ligation, or STUbL [Perry, Tainer, and Boddy, Trends Biochem Sci, 2008, 33, 201–208], has significant effects on nuclear functions, ranging from gene regulation to genomic stability. Intersections between SUMO and ubiquitin in protein modification have been the subject of a recent comprehensive review [Praefcke, Hofmann, and Dohmen, Trends Biochem Sci, 2012, 37, 23–31]. Our goal here is to focus on features of enzymes with STUbL activity that have been best studied, particularly in relation to their nuclear functions in humans, flies, and yeasts. Because there are clear associations of disease and development upon loss of STUbL activities in metazoans, learning more about their function, regulation, and substrates will remain an important goal for the future. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 146–154, 2013.